Preparation and Catalytic Performance of Ionic Liquid Catalyst Immobilized by ZrO2 - Lian, Jianwei; Xia, Jianling; Huang, Kun; Li, Mei (Asian Journal of Chemistry, 2013)
A novel Brønsted acidic ionic liquid catalyst [HSO3-bmim]+[HSO4]– loaded by ZrO2 was prepared under impregnation method and characterized by means of X-ray diffraction, FT-IR spectroscopy, thermogravimetric analysis-derivative thermogravimetry, scanning electron microscope and element analysis. The results showed that the capacity of ionic liquid [HSO3-bmim]+[HSO4]- was 21.01 %. The catalyst can be used in the esterification of maleic anhydride and iso-octanol and the convertion rate of maleic anhydride was 99.8 % under the following conditions: 140 ºC, maleic anhydride 0.05 mol, iso-octanol 0.2 mol, toluol 6 g, catalyst 0.8 g and reaction time 100 min. The esterification could still reach to 94.9 % after the catalyst was reused for 9 times. The catalyst has exhibited good thermal stability and repeatability performance.